Discourse Analysis of Political Campaign Messages of Two Candidates for Regent of Banyuwangi 2024 on Instagram - Nurul Yaqin, Muhamad; Wazis, Kun; Raudhatul Jannah, Siti (Electronic Journal of Education, Social Economics and Technology, 2024)
Instagram social media is often used by the public for various purposes. No exception in the political world began to use Instagram social media in its activities. As in campaign activities during the 2024 Regional Head Election (Pilkada) moment. One of them is the use of Instagram social media in campaign tools to attract the attention of potential voters. As is happening in the middle of the 2024 Banyuwangi Regency Pilkada campaign. Where two pairs of cabup-cawabup candidates in the upcoming 2024 Pilkada have utilized Instagram as a campaign tool that contains messages from each candidate pair (Paslon). This was done by candidate pair number 1 Ipuk-Mujiono, and candidate pair number 2 Ali-Ali. This study aims to determine the campaign messages on each candidate pair's Instagram account in the 2024 Banyuwangi Regency Pilkada. The type of research used is descriptive qualitative research using the Teun A Van Dijk model discourse analysis method through analyzing the dimensions of text, social cognition, and social context.